The Development of Senior High School Students’ Worksheet Based on Chemo-Entrepreneurship (CEP) Approach on the Topic of Colloid - Habibati Habibati; Zulfadli Zulfadli; Rizki Amalia (Proceedings of AICS - Social Sciences, 2016)
This study aim was to determine the feasibility of the LKS based on CEP approach and to evaluate the response of teachers and students against LKS-based CEP approach. The subjects were 4 chemistry teachers and 27 students of class XI IPA 3 SMAN 9 Banda Aceh that consists of 16 male and 11 female students. This research type was the Research and Development (R D) with 4-D models, namely the define phase, design phase, develop phase, and the disseminate phase. The data was collected through LKS validity test, questionnaires, and observation. The research instrument used was the observation sheets of students’ activities, attitudes and skills; the cognitive test, the questionnaire sheet of teachers’ and students’ response, and LKS. Based on the validation result from 2 validators, the feasibility result of LKS based CEP approach obtained was 94.6%, which can be interpreted very valid. The response of teachers to LKS based CEP approach can be interpreted very well, in which 84.4% gave positive responses and 15.6% gave negative responses. While the students' responses to LKS based CEP approach can also be interpreted  very  well,  where  81% gave  positive  responses and  19% gave  negative responses. Based on the results of this study, it can be concluded that LKS based CEP approach on the colloid topic was well received by the user so that it can be used as a learning material which can trigger the students to be entrepreneur.